Supervised pratice in community social psychology: Experience report in a therapeutic Community in Teresina-PI (Research, Society and Development, 2024)
The internship in psychology allows the student to develop skills and abilities for the future exercise of their profession. Carrying out the institutional diagnosis in the social device where the supervised internship was carried out, followed by the development of the action plan, included actions and activities aimed at developing intervention models to be applied in the community. The objective of this study is to report the internship experience in the mandatory curricular subject Supervised Internship I, with an emphasis on community social psychology, carried out from October to December 2021, weekly, on Thursdays, at the Manantial da Vida Therapeutic Community, in Teresina -PI. The main demands were identified: anxiety, depression, self-control, impulsivity and overcoming chemical dependency. The interventions were effective, as the group adhered to the proposal presented by the team, demonstrating cohesion, good receptivity and ability to reflect on the topics discussed. In general, common desires were shared, including returning to the social environment and the difficulties and consequences of leaving the therapeutic community.